Optimization of Activated Charcoal Synthesis from Sugar Palm Shells for the Adsorption of Iron Ions in Batik Waste - Oktavianty, Herawati; Sunardi, Sunardi; Laksono, Elfandra Pramudito (Universitas PGRI Madiun, 2021)
Efforts have been made to improve the synthesis of activated charcoal from sugar palm shells (Arenga pinnata). Therefore, the purpose of this study was to use the activated charcoal from sugar palm shells to adsorb Iron (Fe) ions contained in batik waste. Charcoal was activated with a 20-30% phosphoric acid solution (H3PO4), dried at 110 °C for 3 hours, and then calcined at a range of 700-900 °C for 3-5 hours. The results demonstrated that the optimal adsorption of Fe ions was achieved under conditions of 25% H3PO4 concentration, calcination at 800 °C for 4 hours, yielding 46.94% adsorbed Fe, and the largest surface area of 45.087 m2/g.